Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x-\left(25-x\right)=x-17\)
\(\Rightarrow x-25+x=x-17\)
\(\Rightarrow x-x-25+x=17\)
\(\Rightarrow-25+x=17\)
\(\Rightarrow x=17-\left(-25\right)\)
\(\Rightarrow x=42\)
Vậy x = 42
\(1+2+.........+n=741\)
\(\Leftrightarrow\frac{n\left(n+1\right)}{2}=741\)
\(\Leftrightarrow n\left(n+1\right)=1482\)
\(\Leftrightarrow n\left(n+1\right)=38.39\)
\(\Leftrightarrow n=38\)
Vậy \(n=38\)
\(1+2+...+n=\)\(741\)
\(\Leftrightarrow\frac{n.\left(n+1\right)}{2}=741\)
\(\Leftrightarrow n.\left(n+1\right)=741.2\)
\(\Leftrightarrow n.\left(n+1\right)=1482\)
\(\Leftrightarrow n.\left(n+1\right)=38.\left(38+1\right)\)
\(\Rightarrow\)\(n=38\)
Vậy \(n=38\)